Inhibitory Activity of Native Strains of Trichoderma Sp. Isolated from Yam Crops with Inhibitory Activity Against Phytopathogenic Fungi - Cordero, Alexander Pérez; Vergara, Donicer E. Montes; Mendoza, Yelitza Aguas (Journal of Ecohumanism, 2024)
Colletotrichum gloesporioides is one of the main phytopathogens causing limiting diseases in the production of Dioscorea spp. yam (Dioscoreaceae) in the Caribbean region. The objective of the study was to evaluate the antagonistic activity of Trichoderma spp. against C. gloesporioides and its in vitro plant growth promoting potential. Trichoderma harzianum, T. atroviride and T. asperellum species showed inhibition against the pathogen (p<0.05) and promoted plant growth. These species release enzymes that can degrade the cell wall of the pathogen causing its death or inhibit its growth through the production of secondary metabolites. The application of Trichoderma spp. mounts in crops confers protection against pathogens and stimulates plant growth in order to obtain a good yield.